Religious Complexity in the Public Sphere Comparing Nordic Countries (Palgrave Studies in Religion, Politics, and Policy, 2018)
This book is an empirical comparative study of the complexity of religion in the public spheres of the five Nordic countries. The result of a five-year collaborative research project, the work examines how increasingly religiously diverse Nordic societies regulate, debate, and negotiate religion in the state, the polity, the media, and civil society. The project finds that there are seemingly contradictory religious trends at different social levels: a growing secularization at the individual level, and a deprivatization of religion in politics, the media, and civil society. It offers a critique of the current theories of secularization and the return of religion, introducing religious complexity as an alternative concept to understand these paradoxes. This book is for scholars, students, and readers with an interest in understanding the public role of religion in the West. .